From the exotic vase on the table to the pot in the kitchen. Ceramics as a commodity in Sicily: some reflections for an overall analysis of ceramic consumption in the late Middle Ages (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Ceramic vessels are often used in archaeological studies as a proxy for the reconstruction of trade routes, but several aspects of their role in the market have been underestimated. Based on the data collected as part of the European project Sicily in Transition during the study of the ceramic assemblages from the excavations in Mazara del Vallo and Castronovo di Sicilia, this text aims to propose a broader vision of the ceramic object as a commodity by evaluating  the aspects linked to international flows, together with those relating to internal circulation, trying at the same time to consider the changes that occurred in the production and consumption of ceramic objects in Sicily during the 14th and 15th centuries. To do this, three classes of products were selected, showing an evolution that seems indicative of the more general trade dynamics of the period; that is, imported Iberian ceramics, regional ceramics decorated in brown/green and fire ceramics. The complexity that emerged in this study seems indicative of the changes that have occurred in international trade but also of the efficiency of Sicilian internal networks as well as of a great dynamism of the artisan reality of the island.
Keywords: Late Medieval Sicily; Pottery Consumption; Pottery Production